Forest Conservation, Rights, and Diets: Untangling the Issues - Sunderland, Terence C.; Vasquez, Winy (Frontiers in Forests and Global Change, 2020)
Recent research has highlighted the contributions of forests and tree-based systems to both dietary diversity and nutrition as well as agricultural production in the form of tree-based ecosystem services. Wild foods provide a significant nutritional contribution to the diets of rural dwellers, the majority of whom would be classified as some of the world’s poorest. Yet, despite the important human-forest interactions and relative degrees of forest dependency, access to much of the global forest estate is increasingly regulated under the guise of biodiversity conservation. How this restricted access plays out when the “right to food” is a deeply enshrined human right has been deeply contested, particularly with regard to land annexation. This paper outlines the critical issues related to the dietary diversity and nutrition in the context of the availability of wild foods juxtaposed with the growing call for the annexation of land for conservation. We suggest that a more integrated and equitable approach to land management that embraces both biodiversity conservation and broader food security and nutrition goals can provide multiple benefits, while mitigating local conflicts. As such, a rights-based approach to conservation and an embracing of broader landscape perspectives are possible strategies to achieve these seemingly conflicting agendas.